PENGARUH BEBERAPA TINGKAT KEMASAKAN TERHADAP VIABILITAS BENIH TANAMAN ROSELA (Hibiscus sabdariffa L.) - Muhdan Syarovy; Haryati Haryati; Ferry Ezra T Sitepu (Jurnal Agroekoteknologi, 2013)
Roselle is plant that have benefit for the prevention of disease. In Indonesia, productivity of roselleis still low. One factor contributing to low plant productivity is the low quality of the seeds. The lowquality of seeds have low vigor and viability. The aim of the research was to determine the viabilityof seeds roselle (Hibiscus sabdariffa L.) at different levels of ripening are conducted in SeedTechnology Laboratory, Faculty of Agriculture, University of North Sumatra, Medan with a altitude± 25 m above sea level from May until July 2012 using completely randomized design with 6 levelof ripening that is 17 HSMB (day after anthesis flower), 21 HSMB, 25 HSMB, 29 HSMB, 33HSMB dan 37 HSMB. Parameters measured were seed dry weight, moisture content, germinationpercentage normal and seedling dry weight. The results showed that the level of ripeningsignificantly affect seed dry weight, moisture content, percentage normal germination and seedlingdry weight